Patient Engagement in Health and Well-Being: Theoretical and Empirical Perspectives in Patient Centered Medicine - Guendalina Graffigna (Frontiers Research Topics, 2018)
At present citizens are more aware of their health and care rights and more literate about their disease. Furthermore the continuous development of technological and bio-medical solutions are alimenting the expectation for longer and better life expectancy, even despite the diagnosis. Patients require to be higher involved in the decision making about their care and are willing to deeply entangle all the possible treatment options, their advantages, and their risks. In other terms, citizens today want to be treated not only as "client" but mainly as partners of the medical action and as co-authors of the success of their healthcare pathway. Due to this socio-psychological change in patients' attitude, healthcare systems today are claimed to a deep revision of their practices and organizational models in order to become better responsive to patients' expectation and more sustainable and effective in the management of their services. Patient participation and engagement in healthcare management, indeed, is today acknowledged by policy makers and healthcare experts as a valuable option to orient changes and actions of the healthcare systems. Several empirical studies have demonstrated the positive outcomes of a participatory care approach at the clinical, psychosocial, and economic levels. Patient Engagement, thus, appears today not only an ethical but also a pragmatic imperative for the innovation and the improvement of healthcare system. Moving from these premises, this e-book collects first research experiences, conceptual contribution and review of good practices in the area of Patient Engagement promotion. The e-book also discusses the relevance and the theoretical linkages between the concept of Patient Engagement and that one of Patient Centered Medicine.